A carbon sheet containing nickel-doped porous carbon and its preparation method and application

By doping nickel and nitrogen into porous carbon materials, nickel-doped porous carbon sheets were prepared, solving the problems of conductivity and structural stability in sodium-ion batteries and achieving a significant performance improvement in sodium-ion batteries.

CN115172744BActive Publication Date: 2025-01-10BOZHOU YAZHU NEW MATERIAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210933031.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-04
Publication Date
2025-01-10
Estimated Expiration
2042-08-04

AI Technical Summary

Technical Problem

In sodium-ion batteries, traditional graphite-based carbon electrode materials have poor conductivity and are prone to structural collapse, resulting in insufficient cycle performance and rate performance, which cannot meet the capacity and cycle stability requirements of sodium-ion batteries.

Method used

Nickel-doped porous carbon sheets are used. By doping the porous carbon material with nickel and nitrogen, the conductivity and structural stability are enhanced, forming micropore and macropore structures, thereby increasing the porosity and specific surface area of ​​the electrode material.

Benefits of technology

It enhances the rate performance and cycle stability of sodium-ion batteries, improves the electrochemical active sites of electrode materials, increases the storage capacity and conductivity of sodium ions, avoids structural collapse, and maintains a high capacity retention rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115172744B_ABST
    Figure CN115172744B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of new energy materials, and discloses a carbon sheet containing nickel-doped porous carbon, a preparation method and an application thereof. The porous carbon nanosheet is doped with nickel and nitrogen to enhance the toughness of the porous carbon nanosheet material. Meanwhile, the doped nitrogen and nickel can form a synergistic effect to further enhance the conductivity of the porous carbon nanosheet. Therefore, the volume expansion of the porous carbon nanosheet caused by the continuous deintercalation / intercalation of sodium ions during the continuous charge and discharge process, and the phenomenon of structural collapse can be effectively avoided, thereby achieving the effect of enhancing the cycle stability of a sodium ion battery. The carbon sheet is applied to the electrode material of a sodium ion battery to have good rate performance and cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy materials, and in particular to a carbon sheet containing nickel-doped porous carbon, and a preparation method and application thereof. Background Art

[0002] In recent years, lithium-ion batteries have developed rapidly, the technology has become mature, and they are widely used in portable electronic devices and electric vehicles. They have gradually replaced some fossil energy, built a storable clean energy storage system, and solved the environmental problems caused by fossil energy consumption. However, the lithium metal content is low and the price is high, making it difficult to maintain long-term development. Therefore, it is necessary to develop new energy storage devices to replace lithium-ion batteries. Sodium and lithium belong to the same main group and have similar energy storage mechanisms. Therefore, they are expected to replace lithium-ion batteries and become new energy storage devices.

[0003] Although the energy storage mechanism of sodium and lithium is similar, the atomic radius of sodium ions is much larger than that of lithium ions. During the charge and discharge process of the battery, it is difficult to achieve a faster insertion and deinsertion speed, which makes the battery efficiency low, and the cycle performance and rate performance cannot be guaranteed. Traditional graphite-based carbon-based electrode materials are not highly conductive and their structures are prone to collapse, which cannot meet the requirements of capacity and cycle stability of sodium ion battery electrode materials. Therefore, it is necessary to develop electrode materials with excellent performance to solve the problems faced in the current research and development process. Patent No. CN110240160A discloses a sodium ion The invention discloses a method for preparing boron-doped biomass porous carbon nanoelectrode materials for batteries. By doping the biomass porous carbon materials with boron, the diffusion rate of sodium ions and the electron transport performance are improved, which is beneficial to enhancing the conductivity of the porous carbon materials, thereby making the sodium ion battery prepared with the porous carbon materials as the main active electrode material have good rate performance. However, this scheme does not solve the problem that the porous carbon materials themselves are prone to structural collapse and cannot ensure the cycle stability of the sodium ion battery. Therefore, modifying the porous carbon materials and avoiding the above-mentioned problems are important directions for developing new sodium ion battery electrode materials. Summary of the invention

[0004] The purpose of the present invention is to provide a carbon sheet containing nickel-doped porous carbon and its preparation method and application. By doping the porous carbon material with nickel and nitrogen, not only the rate performance of the porous carbon material is enhanced, but also the problem of poor cycle stability of the porous carbon material can be improved.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A carbon sheet containing nickel-doped porous carbon, the carbon sheet containing nickel-doped porous carbon having micropore and macropore structure, pore diameter of 20-2000nm, pore volume of 0.5-4cm 3 / g, specific surface area is 100-3000m 2 / g, and the nickel doping amount is 15%-25%.

[0007] Furthermore, a specific method for preparing a carbon sheet containing nickel-doped porous carbon comprises the following steps:

[0008] S1: Add nickel acetate to 20-40 mL of a mixed solvent of ethylene glycol and deionized water, mix well, and continue to add modified cellulose under stirring, mix well, and obtain a mixed solution;

[0009] S2: pour the mixed solution prepared in step S1 into a reaction kettle, seal it, transfer it to an oven, heat it at 170-190° C. for 24-36 hours, and after the product is cooled, collect the product by centrifugation, wash it with ethanol and deionized water for 1-3 times, and then vacuum dry it to obtain a carbon precursor;

[0010] S3: Add the carbon precursor prepared in step S2 to the alkaline aqueous solution, stir and mix evenly, evaporate the solvent, transfer it to a tube furnace, activate and make holes at 200-400°C for 6-18h, and after the product is cooled, wash the product with hydrochloric acid and deionized water in turn, and vacuum dry it to obtain an activated carbon precursor;

[0011] S4: placing the activated carbon precursor prepared in S3 in a tubular furnace for carbonization treatment, and after the product is cooled, obtaining a doped porous carbon nanosheet, that is, a carbon sheet containing nickel-doped porous carbon.

[0012] Furthermore, in step S1, the volume ratio of ethylene glycol to deionized water is 1:1.

[0013] Furthermore, the alkaline aqueous solution in step S3 is a potassium hydroxide or sodium hydroxide aqueous solution with a mass concentration of 2-5%.

[0014] Furthermore, the carbonization treatment in step S4 is carried out under the following conditions: heating to 700-850° C. at a heating rate of 1-3° C. / min, and carbonizing for 1-3 h under nitrogen protection.

[0015] Through the above technical scheme, nickel acetate is first hydrolyzed to generate Ni 2+ and acetate ions, Ni 2+ It can react with ethylene glycol to form a compatible complex. The acetate ion reacts with water to form acetic acid and ionizes to produce OH - , the OH - with Ni 2+The nickel hydroxide core is reacted to generate a nickel hydroxide core, which is released and regulated by the complex dissociation equilibrium and the hydrolysis equilibrium to form a nickel hydroxide nanosheet, and the microspheres generated by the modified cellulose in the hydrothermal process are adsorbed on the strong nickel oxide nanosheet, and finally a carbon-coated nickel hydroxide nanosheet is formed. The carbon is then activated with an alkaline solution to form pores and subjected to a high-temperature carbonization process, and the nickel hydroxide is gradually reduced to nickel, and finally a doped porous carbon nanosheet is obtained, that is, a carbon sheet containing nickel-doped porous carbon of the present invention.

[0016] Furthermore, the preparation method of the modified cellulose includes: adding carboxymethyl cellulose to N,N-dimethylformamide solvent, stirring thoroughly, continuing to add 2-amino-3-hydroxypyridine, dicyclohexylcarbodiimide and 4-dimethylaminopyridine, mixing, placing it in a water bath at 15-40°C, stirring for reaction for 12-24 hours, after the reaction is completed, centrifuging the product, and obtaining the modified cellulose through precipitation and vacuum drying processes.

[0017] Furthermore, the N,N-dimethylformamide is 80-150 parts, the mass fraction of carboxymethyl cellulose is 1 part, the mass fraction of 2-amino-3-hydroxypyridine is 0.6-1.5 parts, the mass fraction of dicyclohexylcarbodiimide is 0.5-1.2 parts and the mass fraction of 4-dimethylaminopyridine is 0.02-0.06 parts.

[0018] Through the above technical scheme, under the composite catalytic action of dicyclohexylcarbodiimide and 4-dimethylaminopyridine, the carboxymethyl group in the carboxymethyl cellulose structure can react with 2-amino-3-hydroxypyridine. Since the activity of the amino group is higher than that of the hydroxyl group, in this reaction, the carboxymethyl group in the cellulose undergoes an amidation reaction with the amino group. When the 2-amino-3-hydroxypyridine is excessive, the hydroxyl group can also undergo an esterification reaction with the carboxyl group to a certain extent, thereby forming partially cross-linked cellulose, thereby modifying the pyridine functional group in the cellulose structure by a simple chemical reaction. This chemical connection method can make the pyridine functional group relatively evenly distributed in the structure of the cellulose. Therefore, in the subsequent carbonization process, the pyridine functional group can be used as a nitrogen source and can be evenly doped in the structure of the porous carbon nanosheet. Moreover, the carbonization rate of the cellulose is higher after cross-linking, and the pore structure is richer, thereby further increasing the specific surface area of ​​the porous carbon nanosheet.

[0019] Furthermore, the application of the prepared nickel-doped porous carbon sheet is to apply the prepared nickel-doped porous carbon to the field of electrode materials for sodium ion batteries.

[0020] Beneficial effects of the present invention:

[0021] (1) The carbon material is activated and porous by using an alkaline aqueous solution, so that the final prepared carbon sheet has a rich pore structure. Due to the existence of the pore structure, the electrolyte is easier to infiltrate the carbon material, which increases the reaction contact sites between the active substances of the carbon material and the sodium ions, thereby achieving a high utilization rate of the carbon material and effectively enhancing the rate performance of the carbon material.

[0022] (2) By doping nickel into the porous carbon nanosheets, not only can the excellent conductivity of metallic nickel be combined to improve the conductivity of the porous carbon nanosheets, but the toughness of the porous carbon nanosheets can also be increased through the high strength of the metal itself. Therefore, the volume expansion of the porous carbon nanosheets caused by the continuous extraction / embedding of sodium ions during the continuous charge and discharge process can be effectively avoided, thereby achieving the effect of enhancing the cycle stability of the sodium ion battery. After 1,000 cycles, it still has a capacity retention rate of 91.7%.

[0023] (3) By doping nitrogen into the porous carbon nanosheet structure, the electronic structure of the porous carbon nanosheet can be adjusted to achieve rapid transmission and transfer of sodium ions and electrons in the electrolyte. At the same time, rich active structures such as pyridinic nitrogen, graphitic nitrogen and pyrrolic nitrogen are introduced. Among them, pyridinic nitrogen and pyrrolic nitrogen can construct a stable molecular configuration in the porous carbon nanosheet structure, increase the electrochemical active sites of the porous carbon nanosheet, enhance its adsorption performance for sodium ions, and thus improve the storage capacity of the porous carbon nanosheet for sodium ions, so that it has a higher transfer capacity, thereby improving the specific capacity of the sodium ion battery. At the same time, the doped nitrogen and nickel elements can form a synergistic effect, further enhancing the conductivity of the porous carbon nanosheet, so that it has better rate performance.

[0024] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0026] Figure 1 This is a comparison chart of the XPS full spectra of the nickel-doped porous carbon sheet of the present invention and the ordinary porous carbon material prepared in Comparative Example 3.

[0027] Figure 2 The nitrogen adsorption-desorption isotherm curves of the nickel-doped porous carbon sheet of the present invention and the ordinary porous carbon material prepared in Comparative Example 3. DETAILED DESCRIPTION

[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Example 1

[0030] Preparation of modified cellulose:

[0031] 1 g of carboxymethyl cellulose was added to 100 mL of N,N-dimethylformamide solvent, and the mixture was stirred well. Then, 0.8 g of 2-amino-3-hydroxypyridine, 0.6 g of dicyclohexylcarbodiimide and 0.03 g of 4-dimethylaminopyridine were added and mixed well. The mixture was placed in a water bath at 25°C and stirred for reaction for 18 h. After the reaction, the product was separated by centrifugation. The modified cellulose and unmodified carboxymethyl cellulose were ground into powder and placed in an ICP element analyzer for element content analysis. The test elements included C, H and N. The test results are shown in Table 1.

[0032] Table 1 Element content analysis

[0033] Group C(%) H(%) N(%) Example 1 46.7 5.4 10.6 Unmodified cellulose 41.8 6.1 0

[0034] It can be concluded from the test data in Table 1 that the percentage contents of C, H and N elements in the modified cellulose prepared in Example 1 of the present invention are 46.7%, 5.4% and 10.6%, respectively, and the percentage contents of C, H and N elements in ordinary cellulose are 41.8%, 6.1% and 0%, respectively. The contents of C and N elements have increased to a certain extent, while the H element has decreased. It is speculated that this is due to the introduction of pyridine groups by dehydration condensation of cellulose. Therefore, it can be inferred that the structure of cellulose has changed after modification, and new pyridine groups have been introduced, confirming that the pyridine groups have been successfully grafted into the structure of cellulose.

[0035] Example 2

[0036] Preparation of carbon sheets containing nickel-doped porous carbon

[0037] S1: Add 0.6 g of nickel acetate to 30 mL of a mixed solvent of ethylene glycol and deionized water in a volume ratio of 1:1, mix well, and continue to add 2 g of the modified cellulose prepared in Example 1 of the present invention under stirring, mix well, and obtain a mixed solution;

[0038] S2: pour the mixed solution prepared in step S1 into a reaction kettle, seal it, transfer it to an oven, heat it at 180°C for 24 hours, and after the product is cooled, collect it by centrifugation, wash it with ethanol and deionized water for 3 times, and then vacuum dry it to obtain a carbon precursor;

[0039] S3: Add the carbon precursor prepared in step S2 to a 4% mass concentration of potassium hydroxide alkaline aqueous solution, stir and mix evenly, evaporate the solvent, transfer it to a tube furnace, activate and make holes at 350°C for 12 hours, and after the product is cooled, wash the product with hydrochloric acid and deionized water in turn, and vacuum dry it to obtain an activated carbon precursor;

[0040] S4: placing the activated carbon precursor prepared in S3 in a tube furnace, heating it to 800°C at a heating rate of 2°C / min, and carbonizing it for 2 hours under nitrogen protection. After the product is cooled, a doped porous carbon nanosheet, i.e., a carbon sheet containing nickel-doped porous carbon, is obtained. Figure 1 The XPS full spectrum comparison diagram of the nickel-doped porous carbon sheet and the ordinary porous carbon material prepared in Comparative Example 3 is shown in FIG. Figure 1 It can be seen that compared with the common porous carbon material prepared in Comparative Example 3, the carbon sheet containing nickel-doped porous carbon has a new peak at 397eV, which is the peak of nitrogen element, and new peaks are generated at 855eV and 872eV, which are Ni 2p3 / 2 and Ni 2p1 / 2 The peaks of the nickel-doped porous carbon confirm that the carbon sheet containing nickel-doped porous carbon is successfully doped with nitrogen and nickel. Figure 2 is the nitrogen adsorption-desorption isotherm curve of the nickel-doped porous carbon sheet and the ordinary porous carbon material prepared in Comparative Example 3, Figure 2 It can be seen that under the same relative pressure conditions, the nitrogen adsorption amount of the nickel-doped porous carbon carbon sheet is much greater than that of the ordinary porous carbon material prepared using unmodified cellulose as a carbon precursor in Comparative Example 3, confirming that the nickel-doped porous carbon carbon sheet has a higher porosity and specific surface area. It is speculated that this is due to a certain cross-linking reaction in the modified cellulose, which makes it have a higher carbonization rate and porosity, so the obtained porous carbon nanosheet has a richer pore structure.

[0041] Comparative Example 1

[0042] Preparation of carbon sheets containing nickel-doped porous carbon

[0043] S1: Add 0.6 g of nickel acetate to 30 mL of a mixed solvent of ethylene glycol and deionized water in a volume ratio of 1:1, mix well, and continue to add 2 g of cellulose under stirring, mix well, and obtain a mixed solution;

[0044] S2: pour the mixed solution prepared in step S1 into a reaction kettle, seal it, transfer it to an oven, heat it at 180°C for 24 hours, and after the product is cooled, collect it by centrifugation, wash it with ethanol and deionized water for 3 times, and then vacuum dry it to obtain a carbon precursor;

[0045] S3: Add the carbon precursor prepared in step S2 to a 2-5% mass concentration of potassium hydroxide aqueous solution, stir and mix evenly, evaporate the solvent, transfer it to a tube furnace, activate and make holes at 350°C for 12 hours, and after the product is cooled, wash the product with hydrochloric acid and deionized water in turn, and vacuum dry it to obtain an activated carbon precursor;

[0046] S4: placing the activated carbon precursor prepared in S3 in a tubular furnace, heating it to 800°C at a heating rate of 2°C / min, and carbonizing it under nitrogen protection for 2 hours. After the product is cooled, a doped porous carbon nanosheet, i.e., a carbon sheet containing nickel-doped porous carbon, is obtained.

[0047] Comparative Example 2

[0048] Preparation of doped porous carbon materials

[0049] S1: Add the modified cellulose prepared in Example 1 of the present invention to a 4% mass concentration of potassium hydroxide alkaline aqueous solution, stir and mix evenly, evaporate the solvent, transfer it to a tube furnace, activate and make pores at 350° C. for 12 hours, cool the product, wash the product with hydrochloric acid and deionized water in turn, and vacuum dry it to obtain an activated carbon precursor;

[0050] S2: The activated carbon precursor prepared in S1 is placed in a tubular furnace, heated to 800°C at a heating rate of 2°C / min, and carbonized for 2 hours under nitrogen protection. After the product is cooled, a nitrogen-doped porous carbon material, i.e., a doped porous carbon material, is obtained.

[0051] Comparative Example 3

[0052] Preparation of common porous carbon materials

[0053] S1: Add carboxymethyl cellulose to a 4% mass concentration of potassium hydroxide alkaline aqueous solution, stir and mix evenly, evaporate the solvent, transfer it to a tube furnace, activate and make pores at 350°C for 12 hours, and after the product is cooled, wash the product with hydrochloric acid and deionized water in turn, and vacuum dry it to obtain an activated carbon precursor;

[0054] S2: The activated carbon precursor prepared in S1 is placed in a tubular furnace, heated to 800°C at a heating rate of 2°C / min, and carbonized for 2 hours under nitrogen protection. After the product is cooled, an ordinary porous carbon material is obtained.

[0055] Rate performance and cycle performance tests of the nickel-doped porous carbon sheet prepared in Example 2 of the present invention, Comparative Example 1, the nitrogen-doped porous carbon material prepared in Comparative Example 2, and the ordinary porous carbon material prepared in Comparative Example 3:

[0056] 70 g of the nickel-doped porous carbon sheet prepared in Example 2 of the present invention and Comparative Example 1, and the nitrogen-doped porous carbon material prepared in Comparative Example 2, 20 g of conductive carbon black, and 10 g of polyvinyl pyrrolidone were weighed respectively, poured into a reactor and stirred until a uniform coating liquid was formed, and the coating liquid was evenly coated on a clean copper foil, dried, and cut into electrode sheets with a diameter of 10 mm, with a metal sodium sheet as the counter electrode and a glass fiber as the diaphragm, dissolved in a mixed solution of dimethyl carbonate, diethyl carbonate and ethylene carbonate with a volume ratio of 1:1:1, and LNaPF with a concentration of 1 mol / L 6 The electrolyte was used to assemble button cells, and the specific capacity of the battery at different current densities and the capacity retention rate after 1000 cycles at the same current density were tested using a PARSTAT 3000-DX electrochemical workstation.

[0057] Table 2 Rate performance test

[0058]

[0059] It can be concluded from the test data in Table 2 that the carbon sheet containing nickel-doped porous carbon prepared in Example 2 of the present invention has a specific capacity of 513.8 mAh / g at a current density of 0.1 mA / g. When the current density rises to 3.0 mA / g, the specific capacity can still reach 270.6 mAh / g, so it has good rate performance. The carbon sheet containing nickel-doped porous carbon prepared in Comparative Example 1 is not doped with nitrogen, so the specific capacity at a current density of 0.1 mA / g is relatively low, only 313.1 mAh / g. When the current density rises to 3.0 mA / g, the specific capacity is only 129.4 mAh / g, and the rate performance is poor. The specific capacity of the porous carbon material doped with only nitrogen at a current density of 0.1 mA / g is even lower, only 246.1 mAh / g, and when the current density is increased to 3.0 mA / g, its specific capacity is only 49.5 mAh / g, and the rate performance is also very poor. In comparative example 3, the ordinary porous carbon material without any doping has a specific capacity of only 209.4 mAh / g at a current density of 0.1 mA / g, and a specific capacity of only 29.8 mAh / g at a current density of 3.0 mA / g. Not only is the specific capacity low, but the rate performance is also poor. Therefore, co-doping the porous carbon nanosheets with nickel and nitrogen elements has a significant effect on improving the rate performance of the porous carbon material.

[0060] Table 3 Capacity retention test

[0061]

[0062] It can be concluded from the test data in Table 3 that the carbon sheet containing nickel-doped porous carbon prepared in Example 2 of the present invention has a good capacity retention rate, and the presence of nickel element in the carbon sheet containing nickel-doped porous carbon prepared in Comparative Example 1 improves the toughness of the porous carbon nanosheet material to a certain extent, and therefore also has a relatively good capacity retention rate, but the doped porous carbon material and ordinary porous carbon material not doped with nickel element in Comparative Examples 2 and 3 have poor capacity retention rates, which is presumably because the volume expansion phenomenon is severe during the repeated insertion and extraction of sodium ions, resulting in structural collapse of the porous carbon material.

[0063] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0064] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a carbon sheet containing nickel-doped porous carbon, characterized in that: The specific steps include: S1: Add nickel acetate to 20-40 mL of a mixed solvent of ethylene glycol and deionized water, mix well, and continue to add modified cellulose under stirring, mix well, and obtain a mixed solution; S2: pour the mixed solution prepared in step S1 into a reaction kettle, seal it, transfer it to an oven, heat it at 170-190° C. for 24-36 hours, and after the product is cooled, collect the product by centrifugation, wash it with ethanol and deionized water for 1-3 times, and then vacuum dry it to obtain a carbon precursor; S3: Add the carbon precursor prepared in step S2 to the alkaline aqueous solution, stir and mix evenly, evaporate the solvent, transfer it to a tube furnace, activate and make holes at 200-400°C for 6-18h, and after the product is cooled, wash the product with hydrochloric acid and deionized water in turn, and vacuum dry it to obtain an activated carbon precursor; S4: placing the activated carbon precursor prepared in S3 in a tubular furnace for carbonization treatment, and after the product is cooled, obtaining a doped porous carbon nanosheet, i.e., a carbon sheet containing nickel-doped porous carbon; The preparation method of the modified cellulose comprises the following steps: adding carboxymethyl cellulose to an N,N-dimethylformamide solvent, stirring the mixture thoroughly, adding 2-amino-3-hydroxypyridine, dicyclohexylcarbodiimide and 4-dimethylaminopyridine, mixing the mixture, placing the mixture in a water bath at 15-40°C, stirring the mixture for reaction for 12-24 hours, and after the reaction is completed, centrifuging the product, and performing precipitation and vacuum drying to obtain the modified cellulose.

2. The method for preparing a carbon sheet containing nickel-doped porous carbon according to claim 1, characterized in that: The volume ratio of ethylene glycol to deionized water in step S1 is 1:

1.

3. The method for preparing a carbon sheet containing nickel-doped porous carbon according to claim 1, characterized in that: The alkaline aqueous solution in step S3 is a potassium hydroxide or sodium hydroxide aqueous solution with a mass concentration of 2-5%.

4. The method for preparing a carbon sheet containing nickel-doped porous carbon according to claim 1, characterized in that: The conditions for the carbonization treatment in step S4 are: heating to 700-850° C. at a heating rate of 1-3° C. / min, and carbonization treatment for 1-3 hours under nitrogen protection.

5. The method for preparing a carbon sheet containing nickel-doped porous carbon according to claim 1, characterized in that: The N,N-dimethylformamide is 80-150 parts, the mass fraction of carboxymethyl cellulose is 1 part, the mass fraction of 2-amino-3-hydroxypyridine is 0.6-1.5 parts, the mass fraction of dicyclohexylcarbodiimide is 0.5-1.2 parts, and the mass fraction of 4-dimethylaminopyridine is 0.02-0.06 parts.

6. An application of a carbon sheet containing nickel-doped porous carbon, characterized in that: The carbon sheet containing nickel-doped porous carbon prepared by the method for preparing a carbon sheet containing nickel-doped porous carbon as described in claim 1 is applied in the field of electrode materials for sodium ion batteries.

Citation Information

Patent Citations

  • Preparation method of boron-doped biomass porous carbon nano electrode material for sodium ion battery

    CN110240160A